From native malt to pure starch – Development and characterization of a purification procedure for modified starch. (May 2016) - Rittenauer, M.; Kolesnik, L.; Gastl, M.; Becker, T.
Abstract: Starch characteristics influence the gelatinization process, which is an important prerequisite for the saccharification required in many industrial processes. In order to determine these characteristics in barley malt, an adapted purification procedure allowing to preserve the native starch composition and simultaneously segregating the amylolytic enzymes which were formed during the germination is indispensable. Therefore, this research aimed to develop a method based on a combination of dry milling, micro-sieving and density gradient centrifugation. The impact on the starch characteristics was evaluated for three germinated barley varieties. The purified starches showed starch contents greater than 90% and proteins contents less than 0.4%. Yields ranged from 40.3 to 48.6%, depending on the variety. Considering the starch properties, the amylose/amylopectin ratio was not modified during the purification. The circularity of the granules as well as the ratio of A- and B-type granules remained constant. The particle size distribution of A-granules was not shifted, B-granules with a specific diameter of 5–10 μm were slightly reduced in dependency of the native granule composition. The highest impact could be observed on the amylolytic enzymes, which were completely segregated regardless of their initial value. The standard deviation of repeatability was less than 5%, except for the determination of B-type particle size distribution (7%). The newly developed procedure supplements existing isolation methods of unmalted grains by enabling the purification of germinated barley in a reproducible manner, without altering the native starch properties and by providing pure starch free of amylolytic activity. Graphical abstract: Highlights: An adapted starch purification procedure for germinated barley was developed. 3 barley varieties were germinated, purified and analyzed. Starch content was >90%, protein content <0.4% after the purification. Starch composition was not altered significantly. Amylolytic enzymes were completely segregated during the purification.